KAZGUU Liberal Arts Digest. Volume 2 - Students M.Narikbayev KAZGUU University School of Liberal Arts (M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
“KLAD” is a student journal first published at M. Narikbayev Kazguu University School of liberal arts. This journal is aimed at enhancing students’ involvement into science and research. «KLAD” journal admits for publication various types of articles: original research, review articles, short reports or essays, reflections, case studies, methodologies and cases in english; containing the results of fundamental and applied research in the field of philosophy and identity, history of kazakhstan, pedagogy, linguistics and methods of teaching languages, translation, and tourism.
Research articles